Analisis Bibliometrik dari Ketrampilan Proses Sains dan Experiential Learning pada Tahun 2020-2021 - Saputra, Catur Surya; Purnomo, Aris Rudi (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2023)
Bibliometric analysis is a scientific method that can be useful for researchers who wish to pursue broad and rich retrospectives in research. This article is a bibliometric analysis using Scopus indexed journals about experiential learning and Science Process Skills with the help of the VOSviewer application. The aim of this research is to determine the development of research related to science process skills and experiential learning in terms of the distribution of bibliometric maps and research or publication trends in the Scopus database using VOSviewer software. Specifically, this article discusses the development of citations, publication trends, author collaborations, titles, author keywords, abstracts, and country statistics on the topic of experiential learning and Science Process Skills in 2020-2021. The research results show that the results of the analysis show that the number of publications obtained from 2020-2021 was 5,586 types of publications. In the VOSviewer analysis, it can be seen that there are 586 keywords used in articles that were selected using a minimum of 10 occurrences, resulting in 5 clusters that have strong connections. The term